Investigation of the potential of additive manufacturing in hand surgery - Zarkadas, Dimitrios (My University, 2021)
A broken wrist is a common injury after a fall. In most cases, wrist fractures heal uneventfully. However, in some patients, the forearm bones, radius and/or ulna, heal in the wrong position, resulting in deformations. These deformations can lead to a loss of range of motion (ROM) and pain in the wrist. In such cases, corrective surgery is necessary. Precise cutting of the bone and insertion of the surgical plate that holds the bone together after surgery can be aided by custom surgical parts. This is where additive manufacturing (AM) for biomedical applications offers great potential for customized solutions according to the patient’s needs. Surgical guides help place cuts and holes in the right places during surgery. Those guides can be developed during the planning phase and manufactured using polymer AM. For deformities, where the standard plate does not fit well enough to allow full mobility of the wrist after surgery, surgical plates that hold the bone sections in place can be tailored to the specific patient and fabricated with metal AM. Through a case study, this Master’s thesis explores and develops application strategies of AM solutions in reconstructive wrist surgery aiming to create a common link between surgeons and AM engineers. Current practices and the state of the art in wrist surgery are explored, in combination with potential AM solutions. An evaluation of the entire design and manufacturing chain is performed, including consideration for the unique aspects of biomedical applications such as biocompatibility and sterilization of the material. A parametric model of a metal surgical plate is designed and evaluated for use in the case study. Finally future developments required to fully implement the design and processing chain in the medical field are highlighted as well as the cases in which AM can be beneficial.
Keywords: additive manufacturing; reconstructive wrist surgery; surgery planning; AM biomedical applications; parametric modeling